A reappraisal of the mechanisms of action of ketamine to treat complex regional pain syndrome in the light of cortical excitability changes. Issue 5 (May 2018) - Sorel, Marc; Zrek, Naaman; Locko, Blanche; Armessen, Catherine; Ayache, Samar S.; Lefaucheur, Jean-Pascal
Highlights: Ketamine therapy for pain modulates intracortical glutamate/GABA balance. The analgesic effects of ketamine appears to be related to an enhanced GABAergic transmission. Mechanisms of action of ketamine therapy cannot be resumed to an antiglutamatergic modulation. Abstract: Objective: To evaluate the changes in glutamate/GABA balance of intracortical excitability produced by ketamine, delivered at subanaesthetic dose to treat patients with complex regional pain syndrome (CRPS). Methods: In 19 patients with CRPS, we assessed the effect of a 5-day ketamine protocol on various clinical aspects, including pain and depression, and on cortical excitability parameters provided by transcranial magnetic stimulation testing. Results: The rest motor threshold (RMT) and the amplitude of the motor evoked potentials at 120% of RMT were not modified after ketamine therapy. In contrast, ketamine reduced intracortical facilitation (ICF) in both hemispheres and increased short-interval intracortical inhibition (SICI), which was defective at baseline only in the hemisphere corresponding to the painful side. These changes positively correlated with pain relief. Conclusion: This study shows for the first time that the remarkable analgesic effects produced by ketamine in CRPS patients is associated with cortical excitability changes in favour of an enhanced GABAergic transmission in the hemisphere corresponding to the painful side and an overall reduction of excitability in the contralateral hemisphere. Significance: Analgesic effects of ketamine cannot be resumed to its classical antigutamatergic action related to N-methyl-d -aspartate receptor blockade.